Introducing the medieval ass - Smithies, Kathryn L. (Cardiff : University of Wales Press, 2020)
"Introducing the Medieval Ass presents a lucid, accessible, and comprehensive picture of the enormous socioeconomic and cultural significance of the ass, or donkey, in the Middle Ages and beyond. In medieval times, the ass was a vital, utilitarian beast of burden, rather like ubiquitous white delivery vans today. At the same time, however, the ass had a rich, paradoxical reputation. Its hard work was praised but its obstinacy condemned. It exemplified the good Christian, humbly bearing Christ to Jerusalem, but also represented sloth, a mortal sin. It had a potent sexual reputation--in one literary work, an ass had sex with a woman--even as it was simultaneously linked to sterility. Over time, the ass also became synonymous with human idiocy, a comic figure representing foolish peasants, students too dull to learn, and their asinine teachers. This trope of foolishness was so prevalent that by the eighteenth century the word "ass" began to be replaced by "donkey." Introducing the Medieval Ass offers a wide-ranging account of the importance, and often surprising cultural prevalence, of this common domesticated animal."
The natural world of the ass -- The religious ass -- The scholastic ass -- The ass in literature -- Postscript : the medieval ass in the post-medieval era.
Includes bibliographical references and index.
Kathryn L. Smithies is a medieval historian, and research and teaching associate in the School of Historical and Philosophical Studies at the University of Melbourne.
Print version record.
JSTOR
Keywords: English literature -- Middle English, 1100-1500 -- History and criticism; Donkeys in literature; Littérature anglaise -- 1100-1500 (Moyen anglais) -- Histoire et critique; Âne dans la littérature.; HISTORY / Europe / Medieval; Donkeys in literature; English literature -- Middle English; 1100-1500; Literary criticism; Criticism, interpretation, etc; Literary criticism; Critiques littéraires.